Study of aging behavior of 9/70/30 and 9/65/35 PLZT by optical interferometric technique - Somwan,S. (Elsevier Limited, 2015)
© 2015 Elsevier Ltd and Techna Group S.r.l. In this work Pb0.91La0.09(Zr0.70Ti0.30)0.9775O3 PLZT (9/70/30) and Pb0.91La0.09(Zr0.65Ti0.35)0.9775O3 PLZT (9/65/35) ceramics were prepared at four different sintering temperatures by solid solution method. The samples were aged by keeping at room temperature for 19 days. After the aging process, structural and electrical properties of the samples were studied using Modified Michelson Interferometer, LCR meter and X-ray diffraction. The effect of the Zr/Ti ratios on the dielectric and ferroelectric properties was also investigated. The aged PLZT (9/70/30) showed pinched P-E loop and remnant strain in rhombohedral phase, while PLZT (9/65/35) showed distort s-E shape implying non-180° domain in tetragonal phase.